2022
DOI: 10.1007/s11224-022-01910-6
|View full text |Cite
|
Sign up to set email alerts
|

A density functional theory study on the water aggregation behaviour of fatty acid-based anionic surface active ionic liquids

Abstract: The hydrogen bond interactions between methyl-imidazolium cation (MIM + ) and fatty-acid anions (C m H n COO -, where m=1-6; n-3-13) of ionic liquids are studied in both gas phase and water phase using density functional theory. The structural properties show that the presence of N-H m=1-6;n-3-13) ionic liquids. From the vibrational frequency analysis it was found that the hydrogen bond interaction between [MIM] + and [C m H n COO] -(m=1-6;n-3-13) ionic liquids are red-shifted in frequency. The natural bond or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Table reports the lengths and bond angles for each group of atoms. It is observed that the C–C, S–C, and C–H bonds did not present changes in vacuum and aqueous medium [employing COSMO (COnductor-like Screening MOdel) as the solvation model, which uses a dielectric constant of 78.4 to simulate the medium] . In contrast, the space between sulfur and iodide shows slight distancing (∼0.33 Å), which increased the interaction capacity with other molecules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table reports the lengths and bond angles for each group of atoms. It is observed that the C–C, S–C, and C–H bonds did not present changes in vacuum and aqueous medium [employing COSMO (COnductor-like Screening MOdel) as the solvation model, which uses a dielectric constant of 78.4 to simulate the medium] . In contrast, the space between sulfur and iodide shows slight distancing (∼0.33 Å), which increased the interaction capacity with other molecules.…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that the C–C, S–C, and C–H bonds did not present changes in vacuum and aqueous medium [employing COSMO (COnductor-like Screening MOdel) as the solvation model, which uses a dielectric constant of 78.4 to simulate the medium]. 96 In contrast, the space between sulfur and iodide shows slight distancing (∼0.33 Å), which increased the interaction capacity with other molecules. As for the bond angles of the different atom groups, they presented negligible variations when the medium was changed, suggesting that the distribution of the [DDMS + I – ] atoms was not affected.…”
Section: Resultsmentioning
confidence: 99%